Relationship of follow-through movements to target accuracy in compound archers - Song, J.; Kim, K. (Korean Journal of Sport Biomechanics, 2024)
Objective: This study aimed to investigate how the movements occurring during the follow-through phase after releasing an arrow among elite compound archers, are associated with the arrow impact points on the target. Method: Nine elite archers performed consecutive compound archery shooting under conditions identical to actual competitions using their own bows and equipment. Motion capture system and force platform were utilized to record the changes in joint positions and center of pressure, respectively. Principal component analysis was employed to identify the patterns in which multidimensional joint positions and COP changes were organized with horizontal and vertical coordinates of arrow impact points. Subsequently, correlation analysis quantified the relationship between individual variables and the coordinates of arrow impacts on the target. Results: We found a common organizational pattern in which the two axes of the impact point coordinates were grouped into the first two principal components. The movements of the upper and lower limbs following release exhibited opposite patterns in the anterior-posterior axis, with significant correlations observed between the arrow impact points of the horizontal axis and the left shoulder, right elbow, left hip, and both knees. Additionally, the lateral movements induced by the reaction force upon arrow release showed significant associations with the vertical coordinates of the impact points. Particularly, the correlations between the movements of the left shoulder and elbow, as well as the bilateral hip and right knee, were consistently observed among all participants. Conclusion: These findings implied that the post-release movements could significantly influence the trajectory and impact points of the arrows in compound archery. We suggest that a consistent and controlled movement during the follow-through phase may be more beneficial for optimizing shooting accuracy and precision rather than minimizing movements.